Effect of Intramuscular Protons, Lactate, and ATP on Muscle Hyperalgesia in Rats - Gregory, Nicholas S.; Whitley, Phillip E.; Sluka, Kathleen A. (PloS one, 2015)
Chronic muscle pain is a significant health problem leading to disability[1]. Muscle fatigue can exacerbate muscle pain. Metabolites, including ATP, lactate, and protons, are released during fatiguing exercise and produce pain in humans. These substances directly activate purinergic (P2X) and acid sensing ion channels (ASICs) on muscle nociceptors, and when combined, produce a greater increase in neuron firing than when given alone. Whether the enhanced effect of combining protons, lactate, and ATP is the sum of individual effects (additive) or more than the sum of individual effects (synergistic) is unknown. Using a rat model of muscle nociceptive behavior, we tested each of these compounds individually over a range of physiologic and supra-physiologic concentrations. Further, we combined all three compounds in a series of dilutions and tested their effect on muscle nociceptive behavior. We also tested a non-hydrolyzable form of ATP (α,β-meATP) alone and in combination with lactate and acidic pH. Surprisingly, we found no dose-dependent effect on muscle nociceptive behavior for protons, lactate, or ATP when given alone. We similarly found no effect after application of each two-metabolite combination. Only pH 4 saline and α,β-meATP produced hyperalgesia when given alone. When all 3 substances were combined, however, ATP (2.4μm), lactate (10mM), and acidic pH (pH 6.0) produced an enhanced effect greater than the sum of the effects of the individual components, i.e. synergism. α,β me ATP (3nmol), on the other hand, showed no enhanced effects when combined with lactate (10mM) or acidic pH (pH 6.0), i.e. additive. These data suggest that combining fatigue metabolites in muscle produces a synergistic effect on muscle nociception.